The scope of liquid biopsy in the clinical management of oral cancer. Issue 5 (May 2022) - Baby, N.T.; Abdullah, A.; Kannan, S.
Abstract: Oral squamous cell carcinoma (OSCC) is one of the most prevalent forms of head and neck cancer, and it remains a leading cause of death in developing countries. Failure to detect the disease at an early stage is the main reason for the lack of improvement in the overall survival rate over the decades. Even though tissue biopsy is considered as the gold standard for diagnosis and molecular workup, it is an invasive, expensive and time-consuming procedure. Besides, it may not indicate the genetic status of the entire tumour owing to the heterogeneity of the cancer. In this context, liquid biopsy could be quite useful as it provides a more representative picture of the circulating tumour cells, circulating tumour DNA, circulating RNA, and tumour-derived exosomes obtained from all types of body fluids. This technique provides real-time assessment of variations in the molecular profile of the whole tumour and enables the serial monitoring of the disease status. The method has many advantages, such as easy accessibility, reliability, reproducibility and the possibility for early detection of the disease. However, the concept is still in its infancy, and the research on its application in various tumours including OSCC is rapidly progressing.